Childhood vaccinations. Validation of a tool for measuring knowledge, attitudes and vaccine hesitancy in pregnant women (Epidemiology, Biostatistics, and Public Health, 2022)
Background. The objective of this pilot study was to test a questionnaire aimed at assessing knowledge of and attitudes towards vaccination, as well as intention to vaccinate, among pregnant women.Methods. The questionnaire was self-administered by 49 pregnant women attending antenatal classes at three Family Centers in Rome.Results. Poor knowledge of vaccinations, inadequate attention from healthcare professionals, recurrent consultation of unreliable sources of information, and misconceptions about the side effects of vaccines, all contribute to vaccine hesitancy. Where appropriate, questionnaire sections were shown to be internally consistent.Conclusion. The questionnaire proved reliable and is suitable for further studies.